Why is it necessary to screen for periodontal disease in diabetic patients? - Rucsandra Elena Danciulescu Miulescu; Diana Loreta Paun; Loreta Guja; Oana Alexandra Mladin; Radu Ilinca; Iosif Cosmin Trebuian; Iuliana Gherlan (Romanian Medical Journal)
Periodontal diseases include gingivitis (inflammation of gingiva caused by the bacterial biofilm) and periodontitis involving loss of the supporting structures around the teeth, respectively cementum, periodontal ligament and alveolar bone. Diabetes increases the risk of periodontal diseases; the plausible mechanisms are: alterations in the immunoinflammatory response of bacteria, increased bone loss, the decrease in matrix-producing cells to maintain the periodontium, microvascular changes and alteration in collagen synthesis and metabolism. Treatment of periodontitis influence glycemic control in diabetic patients and intervention trial suggests that this can generate a reduction of circulating inflammatory markers and improves metabolic control in diabetic patients. International forums recommend oral examination as a component of medical care for diabetic patients. Our review summarizes current information on the association of diabetes with periodontal disease.